2021
DOI: 10.1109/access.2021.3112228
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying Blockchain Technology for Resource-Constrained IoT Devices: Parameters, Challenges and Future Perspective

Abstract: One of the most promising enablers for the secure distributed operation of the Internet of Things (IoT) systems could be based on a mathematical construct widely known as blockchain that aims to neglect the system's centralization and scalability properties. This paper aims to map the requirements and features of both systems, highlight the main integration challenges, and technological candidates for smoother integration of IoT and blockchain, as well as highlight the standartization outlook. This work has id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…As the blockchain size increases, processing power, storage, and throughput need also increase or it will not be possible for all nodes to process blocks at some point [54]. The limitation of results consider 3 peers in blockchain, 1 being the orderer in a standard t2.micro AWS machine.…”
Section: Discussionmentioning
confidence: 99%
“…As the blockchain size increases, processing power, storage, and throughput need also increase or it will not be possible for all nodes to process blocks at some point [54]. The limitation of results consider 3 peers in blockchain, 1 being the orderer in a standard t2.micro AWS machine.…”
Section: Discussionmentioning
confidence: 99%
“…In IoT deployments, devices' limited computational power, memory, and energy pose challenges for integrating blockchain solutions [110]. Running full blockchain nodes on resource-constrained devices is impractical, and BaaS introduces additional latency and strain on such devices due to network communication and consensus requirements [110]. Moreover, the transparency of public blockchains raises privacy concerns, necessitating privacy-preserving techniques for sensitive IoT data [79].…”
Section: Open Issues and Future Directionmentioning
confidence: 99%
“…This showed that despite both fields having common native synergies and popular applications such as distributed and trustless ledgers or identity verification. Authors showcase the computation limitations of the IoT devices that could directly compromise the security or the consensus of the network if the resources are not adequately handled, proposing in some occasions to sacrifice in some degree the decentralization in favour of increasing the security [33].…”
Section: Related Workmentioning
confidence: 99%

Can We Run Our Ethereum Nodes at Home?

Cortes-Goicoechea,
Mohandas-Daryanani,
Muñoz-Tapia
et al. 2024
IEEE Access